Is East Germany Catching Up? A Time Series Perspective - Bernd Aumann; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
This paper assesses whether the economy of East Germany is catching up with the West German region in terms of welfare. While the primary measure for convergence and catching up is per capita output, we also look at other macroeconomic indicators such as unemployment rates, wage rates, and production levels in the manufacturing sector. In contrast to existing studies of convergence between regions of reunified Germany, our approach is purely based upon the time series dimension and is thus directly focused on the catching up process in East Germany as a region. Our testing setup includes standard ADF unit root tests as well as unit root tests that endogenously allow for a break in the deterministic component of the process. In our analysis, we find evidence of catching up for East Germany for most of the indicators. However, convergence speed is slow, and thus it can be expected that the catching up process will take further decades until the regional gap is closed. – – Dieser Beitrag untersucht den Aufholprozess Ostdeutschlands gegenüber Westdeutschland bezüglich des Wohlstandsniveaus. Betrachtet wird dabei das Produktionsniveau pro Kopf sowie andere makroökonomische Indikatoren wie Arbeitslosenquoten, Lohne und Produktionsniveaus des Verarbeitenden Gewerbes. Im Gegensatz zu anderen Konvergenzstudien, die Regionen des vereinigten Deutschlands analysieren, verwendet der hier herangezogene Ansatz ausschließlich die Zeitreihendimension und konzentriert sich damit direkt auf den Aufholprozess Ostdeutschlands als eine Region. Die hier angewendeten empirischen Ansätze sind zum einen standardmäßige Einheitswurzeltests nach Dickey-Fuller und zum anderen Einheitswurzeltests, die einen Strukturbruch in den deterministischen Komponenten des Prozesses zulassen. In dieser Studie finden sich Anhaltspunkte eines ostdeutschen Aufholprozesses für einen Großteil der betrachteten Indikatoren. Allerdings ist die Konvergenzgeschwindigkeit langsam; dies lässt erwarten, dass der Aufholprozess weitere Jahrzehnte andauern wird, bis sich die Lücke schließt.
urn:nbn:de:101:1-200911032313
Keywords: C12; C32; O11; O47; 330; East Germany; Catching up; Convergence; Unit root tests; Ostdeutschland; Aufholprozess; Konvergenz; Einheitswurzeltests; Wirtschaftliche Anpassung; Entwicklungskonvergenz; Unit Root Test; Neue Bundesländer; Alte Bundesländer; Deutschland